DAMPAK ISU PASAR MODAL TERHADAP PERGERAKAN HARGA SAHAM DENGAN PENDEKATAN ANALISIS TEKNIKAL - Heri Bahtiar (2022)
The capital market is a place to bring together people who want to invest and companies that want to sell their securities to obtain alternative financing that supports their production activities. There are risks in capital market activities that must be considered by capital market participants, this is because of the factors that influence price fluctuation securities being traded. Investors should be able to analyze the stocks they already own using technical analysis which is a technique for predicting prices based on historical maps in order to analyze movement patterns and fundamental analysis. Use Technical analysis is used for risk in choosing stocks and buying or selling decisions with technical analysis with the Fibonacci (Fibonacci retracement), RSI (Relative Strength Index) and MACD indicators. The purpose of the final project is to understand the use of Fibonacci Retracement to measure the strength of a bullish or bearish trend, the RSI can indicate that the company's stock is oversold or overbought. MACD (Moving Average Convergence Divergence) provides signals aimed at predicting trend reversals more precisely to look for buy and sell signals. This study aims to understand the analysis technique of stocks or securities using Fibonacci retracement indicators, Relative Strength Index and Moving Average Convergence Divergence On ANTM, ADRO, and BBCA